Tingkat Kesetaraan Gender dalam Rumah Tangga Peserta Program Kawasan Rumah Pangan Lestari (KRPL) - Audia Rahma; Siti Amanah (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2020)
Sustainable Reserve Food Garden (SRFG) is a program initiated by the Ministry of Agriculture to increase households food security. The program involves the households that consist of men and women in the activities of SRFGP. To see whether the program has addressed gender equality,  the research aims to analyze how the beneficiary households characteristics of SRFG, how men, women in the beneficiary households divides the division of labours and how the external supports towards the implementation of SRFGP. A census was conducted to 46 beneficiary households of SRFGP who are members of the Melati, Dahlia, and Mawar Women's Farmers Group (WFG) also supported by in-depth interviews to six informants including three chiefs of each WFG, chief of combined farmer group (CFG), agricultural extension officer, and the Village Head of Cikarawang. Most of the beneficiary households have a low level of gender equality in the implementation of SRFGP. The results show the issues of subordination and multi burden that experienced by women in the division of labours arises due to strong social value in the community, women are conceived to be responsible to activities such as managing the households and family, whilst men embedded as head of the family and responsibility to protect the family socio-economically.Keywords: gender equality, rural households, SRFGABSTRAKKawasan Rumah Pangan Lestari (KRPL) merupakan program yang dikembangkan oleh Kementerian Pertanian guna memenuhi ketahanan pangan rumah tangga. Program ini melibatkan rumah tangga yang terdiri dari laki-laki dan perempuan dalam kegiatan Program KRPL. Untuk melihat apakah program ini telah menerapkan prinsip kesetaraan gender, penelitian ini bertujuan untuk menganalisis bagaimana karakteristik rumah tangga peserta Program KRPL, bagaimana pembagian kerja dalam rumah tangga peserta dan bagaimana dukungan lingkungan dalam pelaksanaan Program KRPL. Sensus dilakukan terhadap 46 rumah tangga peserta Program KRPL anggota Kelompok Wanita Tani (KWT) Melati, Dahlia, dan Mawar juga didukung wawancara mendalam kepada enam informan yaitu tiga ketua masing-masing KWT, ketua gapoktan, penyuluh pertanian, dan Kepala Desa Cikarawang. Sebagian besar rumah tangga peserta memiliki tingkat kesetaraan gender yang rendah dalam pelaksanaan Program KRPL. Hasil penelitian menunjukkan terdapat Isu subordinasi dan  beban kerja ganda yang dialami perempuan dalam pembagian kerja rumah tangga muncul akibat kuatnya nilai sosial dalam masyarakat yang dominan menempatkan perempuan pada kegiatan mengatur urusan rumah dan keluarga, sementara laki-laki sebagai kepala keluarga lebih dikhususkan untuk melindungi keluarga secara sosial ekonomi.Kata kunci: kesetaraan gender, Program KRPL, rumah tangga di pedesaan